2016
DOI: 10.1111/ene.12944
|View full text |Cite
|
Sign up to set email alerts
|

Neurothrombectomy in acute ischaemic stroke: a prospective single‐centre study and comparison with randomized controlled trials

Abstract: By choosing pragmatic inclusion criteria state-of-the-art IA therapy of a specialized tertiary stroke centre can be safely applied under real-world conditions to a higher percentage of patients with similar success to the recently published RCTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 35 publications
1
22
1
Order By: Relevance
“…Results from clinical trials favoring mechanical endovascular reperfusion treatment (ERT) versus best medical treatment alone [1][2][3][4][5] have substantially changed the acute treatment in patients with ischaemic stroke and large-vessel occlusion (LVO). The positive trial-result data from a few relatively small study populations have suggested that 'real-life' data may provide results similar to or even better than those reported from the trials [6][7][8]. The present study is the first to present national results on outcome after acute endovascular reperfusion treatment (aERT).…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Results from clinical trials favoring mechanical endovascular reperfusion treatment (ERT) versus best medical treatment alone [1][2][3][4][5] have substantially changed the acute treatment in patients with ischaemic stroke and large-vessel occlusion (LVO). The positive trial-result data from a few relatively small study populations have suggested that 'real-life' data may provide results similar to or even better than those reported from the trials [6][7][8]. The present study is the first to present national results on outcome after acute endovascular reperfusion treatment (aERT).…”
Section: Introductionsupporting
confidence: 55%
“…In a single‐center study from Portugal including 77 patients, 65% achieved a 3‐month mRS score of 0–2, whereas 12% of treated patients had died . In a German study of 97 patients treated with mechanical intervention, 40 (41.2%) had a 3‐month mRS score of 0–2, whereas 24.7% died . A Belgium register of 85 patients reported a 3‐month mRS score of 0–2 in 42% of patients but with a mortality of 26%, with a higher mortality in patients with occlusions in the posterior circulation .…”
Section: Discussionmentioning
confidence: 99%
“…The reported rate of SAH in the RCTs was 0.6%-4.9% 2,1,4, 5 and 1%-5.5% for the non-RCTs. 9,11,47,54 The proposed mechanisms for SAH include: intra-procedural vessel perforation or dissections, occult rupture resulting from stretching of the arterioles and venules in the subarachnoid spaces during the process of withdrawing the stent retriever and disruption of the cerebral microvascular barriers. 12,35,55 McCuster and colleagues reported a case of SAH due to rupture of the MCA with resultant diffuse SAH.…”
Section: Subarachnoid Hemorrhagementioning
confidence: 99%
“…Neurological improvement was defined as decrease of >4 points on the NIHSS on discharge as compared to stroke onset [19]. Disability on discharge was measured with the modified Rankin Scale, mRS [16].…”
Section: Methodsmentioning
confidence: 99%